LINGUAGENS ARTÍSTICAS DO BUMBA MEU BOI NO CURRÍCULO DO ENSINO MÉDIO NO MARANHÃO: Uma experiência no Centro de Ensino Manoel Beckman. - BARROS, Ana Déborah Pereira de (2018)
The Maranhão’s Bumba meu boi is part of the rich popular manifestations that we find in Brazil and is a possible way to insert popular culture in school in an effective way. It harmoniously combines the artistic languages (music, dance, theater and visual arts), and for this reason it is shown as a potential work path to be incorporated into the structure of basic education curricula, especially in the curriculum component Art for High School. Based on authors such as Alves and Timbane (2016), Brandão (2008), Borges (2004), Gadotti (1992), Lima (2013), Santos (2011), Silveira (2015) and Zan (2005). objective to conceive a didactic- pedagogical proposal in Art for Schools of High School in Maranhão that aims at the knowledge, valorization and safeguard of Maranhão’s Bumba meu boi as Cultural Patrimony of Brazil. For this, we opted for a mixed research approach, combining quantitative and qualitative elements, following a quasi-experimental research design. Sixty-three high school students participated in this study, being divided into a control group (32) and an experimental group (31) as a way to compare the effectiveness of the didactic-pedagogical proposal. As data collection instruments, we used documentary research, teaching report, audiovisual record, periodic evaluations and two structured questionnaires elaborated specifically for this study: 1) Questionnaire to assess knowledge about the culture of Maranhão’s Bumba meu boi;; 2) Questionnaire for Student Assessment on the Discipline Art in High School. For the latter two cases, we used non-parametric tests with descriptive and inferential statistics. The results show that the students were satisfied with the didactic program, having a significant learning of the content taught, as well as an increase in the students' interest in the content and the discipline taught. Therefore, we can conclude that the in-depth knowledge of their culture provides the citizen with a better knowledge of himself, generating as a consequence of this self-knowledge his definition as a member of a culture.